Technical Guidance on Personal Taxation of Indonesian Young Entrepreneurs Association (HIPMI) of Pandeglang Regency - Refi Pratiwi; Asih Machfuzhoh; Intan Puspanita (EQUATOR SINAR AKADEMIA, 2022)
Hipmi is an organization of young Indonesian entrepreneurs who are united with the aim and purpose of Encouraging, participating in developing the entrepreneurial spirit among the younger generation. This Technical Guidance activity aims to introduce Personal Taxes to young Indonesian entrepreneurs in Pandeglang Regency, this activity also increases entrepreneurs' knowledge of taxation and increases tax awareness. The method of implementing this activity is to record young entrepreneurs who are members of HIPMI by grouping businesses because there is still a lack of understanding about individual taxation from the calculation, payment to reporting stages.